Processes of Survival and Resistance: Indigenous Soldiers in the Great War in Joseph Boyden’s Three Day Road and Gerald Vizenor’s Blue Ravens - Gasztold, Brygida (Studia Anglica Posnaniensia, 2018)
Joseph Boyden’s Three Day Road (2005) and Gerald Vizenor’s Blue Ravens (2014) offer literary representations of the Great War combined with life narratives focusing on the personal experiences of Indigenous soldiers. The protagonists’ lives on the reservations, which illustrate the experiences of racial discrimination and draw attention to power struggles against the White dominance, provide a representation of and a response to the experiences of Indigenous peoples in North America. The context of World War I and the Aboriginal contributions to American and Canadian wartime responses on European battlefields are used in the novels to take issue with the historically relevant changes. The research focus of this paper is to discuss two strategies of survival presented in Boyden’s and Vizenor’s novels, which enable the protagonists to process, understand, and overcome the trauma of war.